Low awareness of influenza vaccination among pregnant women and their obstetricians: a population-based survey in Beijing, China - Wang, Jing (Hum Vaccin Immunother, 2019)
We assessed how an awareness of influenza vaccination might influence both the willingness of pregnant women to be vaccinated and the readiness of obstetricians to recommend antenatal influenza vaccination in Beijing, China. From March to April 2016, we surveyed pregnant women who were attending antenatal clinics at eight hospitals in Beijing, along with obstetricians at the same clinics. Demographic, attitudinal, and behavioral information regarding influenza vaccination were collected using structured questionnaires. Consent and completed questionnaires were obtained from 988 of 1009 pregnant women and 165 of 173 obstetricians. Only 113 (11.4%) pregnant women reported being willing to receive an influenza vaccine during their pregnancies. Willingness to receive an influenza vaccination was positively associated with ever having a history of vaccination or influenza (aOR=6.74, 95%CI: 1.72-26.4, P=0.006), perceiving benefits of vaccination (aOR=1.67, 95%CI: 1.00-2.79, P=0.050), and having a higher level of influenza knowledge (aOR=82.2, 95%CI: 21.7-311.1, P<0.001). Among obstetricians, only 19.4% reported being willing to recommend influenza vaccination to their pregnant patients and 15.2% reported knowledge that influenza vaccination during pregnancy was recommended by China’s National Health Commission. Neither pregnant women nor their obstetricians were aware of Chinese government recommendations that antenatal influenza vaccination should be encouraged and provided. Pregnant women and their obstetricians were ill-informed of the relevant evidence. It is in emergent need to train and disseminate the updated evidence on influenza vaccination to obstetricians. It also warranted more high-quality trials regarding influenza vaccination during pregnancy to address public concern.